Therapeutic Potential of Mesenchymal Stem Cells for Cancer Therapy - Hmadcha, Abdelkrim; Martin-Montalvo, Alejandro; Gauthier, Benoit R.; Soria, Bernat; Capilla-Gonzalez, Vivian (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem cells (MSCs) are among the most frequently used cell type for regenerative medicine. A large number of studies have shown the beneficial effects of MSC-based therapies to treat different pathologies, including neurological disorders, cardiac ischemia, diabetes, and bone and cartilage diseases. However, the therapeutic potential of MSCs in cancer is still controversial. While some studies indicate that MSCs may contribute to cancer pathogenesis, emerging data reported the suppressive effects of MSCs on cancer cells. Because of this reality, a sustained effort to understand when MSCs promote or suppress tumor development is needed before planning a MSC-based therapy for cancer. Herein, we provide an overview on the therapeutic application of MSCs for regenerative medicine and the processes that orchestrates tissue repair, with a special emphasis placed on cancer, including central nervous system tumors. Furthermore, we will discuss the current evidence regarding the double‐edged sword of MSCs in oncological treatment and the latest advances in MSC-based anti-cancer agent delivery systems.